PENGARUH PELAKSANAAN KATEKISASI SIDI TERHADAP KEDEWASAAN IMAN REMAJA GKPPD KUTA KERANGAN RESORT KUTA KERANGAN TAHUN 2019. - Lastri Gajah (IAKN Tarutung, 2020)
This study aims to determine whether there is a positive and significant influence on the implementation of Sidi catechism on the maturity of faith in shaping the maturity of the GKPPD KutaKerangan church. The research hypothesis is that there is a positive and significant influence between the implementation of Sidi catechism on the maturity of adolescent faith GKPPD KutaKerangan Resort KutaKerangan in 2019. This research is a correlational study using descriptive and inferential statistical techniques. The population is all teenagers GKPPD KutaKerangan Resort KutaKerangan in 2019 totaling 160 people. Samples were taken 22% from 160 people = 36 people. The research instrument was a closed questionnaire. The results of the analysis of the value of rxy = 0.434rtable = 0.329 and tcount = 2.809ttable = 2.042 indicate that there is a relationship the implementation of the Sidi catechization with adolescent faith maturity and obtaining the significance of a simple regression equation. Hypothesis testing obtained Fcount = 7.853Ftable = 1.62 then H0 is rejected and Ha is accepted. This study concludes that the implementation of the Sidi catechism affects adolescent faith maturity by 18.83%. In connection with the results of this study, The author provides input for observers, especially leaders and elders of the church to improve the implementation of the Sidi catechization so that the youth's faith grows into adulthood.Keywords: Implementation of Sidi Catechism, Adolescent Faith Maturity.